On the Demand of Environmental Goods with Intertemporally Dependent Preferences - Belbute, José (2013)
In this paper, we use a simple framework to analyze two issues relating the canonical model of environmental economics. The first is related with the consistency between the intertemporal and the instantaneous structure of the utility function. The second is related with to the specific stability and dynamic properties of the model and to its response to relative price and income exogenous changes. We find that, if there is bounded adjacent complementarity in demand for environmental goods, intertemporal independence in the demand for the other goods and if the utility function displays goods separability, then there will be short-run complementarity between the stock of tastes and the financial wealth. Increases in income will rise the long-run demand for environmental good while increases in the relative price will decrease it.